Building Inter-Religious Tolerance among Indonesians Interview with Minister of Religious Affairs Tarmizi Taher - Prasetyo, Hendro (Studia Islamika, 1994)
The relationship between religion and state has influenced all of Indonesian society. Within the Indonesia context, these relationships have undergone several changes and created certain modes from time to time. During the Old Order, pre-1965, religion generally had a strained relationship with the state. The idea of an Islmaic state, as propossed by some Muslim politicans was partly responsible for creating such a situation. Muslims were divided into fractions between those supportive to this idea and these who were not. In the mean time, other parties suspected these divided Muslim of having threatened their posotions as members of this nation. As a result, a traumatic experience was born from the conflict.DOI: 10.15408/sdi.v1i2.860